REPRESENTASI RWA BHINEDA DALAM ANIMASI 2D JAGADHITA SEBAGAI REFLEKSI SELF-ACCEPTANCE GENERASI Z - Della Jessica; Candrasari, M. C. Wara (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2025)
This study explores the representation of Bali’s local wisdom, Rwa Bhineda, in a 2D animated Jagadhita as a reflection of self-acceptance among Generation Z. Rwa Bhineda illustrates the duality of opposing yet complementary forces in life, as depicted through Barong and Rangda. This animation highlights how the concept of balance is applied to teenagers' lives, particularly in facing social pressures and identity-seeking challenges. The research employs the practice-based research method, integrating visual and narrative exploration through observations, expert interviews, and audience testing with Generation Z teenagers. The findings indicate that this animation effectively conveys the philosophy of Rwa Bhineda in a way that is both understandable and relevant to the psychological struggles of today’s youth. Thus, this work has the potential to serve as an effective educational medium in introducing cultural values while fostering self-acceptance in Generation Z.